2018
DOI: 10.3324/haematol.2017.177980
|View full text |Cite
|
Sign up to set email alerts
|

Recurring mutations in RPL15 are linked to hydrops fetalis and treatment independence in Diamond-Blackfan anemia

Abstract: Diamond-Blackfan anemia (DBA) is a rare inherited bone marrow failure disorder linked predominantly to ribosomal protein gene mutations. Here the European DBA consortium reports novel mutations identified in the RPL15 gene in 6 unrelated individuals diagnosed with DBA. Although point mutations have not been previously reported for RPL15, we identified 4 individuals with truncating mutations p.Tyr81* (in 3 of 4) and p.Gln29*, and 2 with missense variants p.Leu10Pro and p.Lys153Thr. Notably, 75% (3 of 4) of trun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…The median age at presentation is 8 weeks, with a median age at diagnosis of 12 weeks. There have been cases of hydrops fetalis 6 , 7 . The male-to-female ratio of cases is approximately 1:1 despite rare cases of X-linked inheritance.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age at presentation is 8 weeks, with a median age at diagnosis of 12 weeks. There have been cases of hydrops fetalis 6 , 7 . The male-to-female ratio of cases is approximately 1:1 despite rare cases of X-linked inheritance.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…However, RPL5 gene mutations have been associated with cleft palate malformation and are the most important rate of malformations in DBA cases 16 , 17 , while RPL11 mutations are associated with the classic triphalangeal thumb 17 . Recently, mutations in the RPL15 gene have been identified in cases of hydrops fetalis in DBA patients 7 , and RPL35a gene mutations are associated with neutropenia.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…RPL15 acts as a ribosomal assembly factor essential for the formation of the 60S subunit [145] and is also directly involved in pre-rRNA processing at the internal transcribed spacer 1 (ITS1) site of the 47S pre-rRNA [146,147]. RPL15 is significantly upregulated in LoVo, HCT-116, SW-480, and SW-620 CRC cell lines compared to non-transformed epithelial cells, and screening of the ONCOMINE 3.0 database (www.oncomine.org) indicated that RPL15 is overexpressed in CRC and associated with disease progression [148].…”
Section: Regulation Of Ribosome Biogenesis By Ribosomal Proteins In Crcmentioning
confidence: 99%
“…Fetal hydrops is a poor prognostic indicator and results from severe intrauterine anaemia. It is a rare manifestation of Diamond-Blackfan, with fewer than 10 cases reported [50]. Specific truncating mutations in the ribosomal protein RPL15 seem to confer the greatest risk of fetal hydrops [50].…”
Section: Thalassaemiamentioning
confidence: 99%
“…It is a rare manifestation of Diamond-Blackfan, with fewer than 10 cases reported [50]. Specific truncating mutations in the ribosomal protein RPL15 seem to confer the greatest risk of fetal hydrops [50]. First line treatment is with glucocorticoids with chronic blood transfusions and stem-cell transplants reserved for glucocorticosteroid non-responders.…”
Section: Thalassaemiamentioning
confidence: 99%